THE IMPACT OF MODIFYING MARKETING APPROACHES ON THE LEVEL OF BUSINESS RESILIENCE IN THE FACE OF CHANGING CONSUMER PATTERNS (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article presents a detailed study of the impact of the transformation of consumer behavior on the change in the marketing approaches of enterprises and their role in shaping business resilience in an unstable market environment. The author analyzes in-depth the key factors that cause changes in consumer patterns, including social, economic and technological challenges arising from the global crises of recent years, such as pandemics, economic fluctuations, geopolitical tensions and changes in the climate situation. These factors are driving significant changes in consumer behavior, including in their priorities, ways of interacting with brands, and expectations for products and services. Attention is focused on the need for an integrated approach to the adaptation of marketing strategies of enterprises, in particular in the context of ensuring business sustainability through the introduction of flexible marketing models. The author considers adaptation tools such as omnichannel communications, personalization of content and offers for different consumer segments, integration of digital technologies into sales and customer service processes. These tools allow companies not only to interact effectively with modern consumers, but also to quickly adapt to changing market conditions, reducing the risks associated with external shocks. One of the important aspects of the study is the analysis of the adaptive potential of marketing strategies as a basis for the formation of enterprise sustainability. The article emphasizes that in conditions of high instability it is important not only to maintain competitiveness but also to actively seek new opportunities for development by adapting strategies to new realities emerging in the market. By integrating the latest marketing technologies, such as process automation and big data analytics, businesses can ensure effective customer relationship management and respond quickly to changes in demand. The paper examines in detail specific examples of companies that have successfully transformed their marketing strategies, while maintaining their competitiveness and ability to respond quickly to changing market conditions. Based on these practices, the author identifies the main principles that helped companies stay afloat during crises, including ensuring transparency of communications with customers, the ability to quickly reorient product portfolios and pricing strategies, and the use of the latest technologies to optimize internal processes. The paper also formulates a number of practical recommendations for improving the effectiveness of management decisions in the field of marketing. In order to achieve long-term viability and sustainability of a business in conditions of high uncertainty, it is necessary to implement strategic planning mechanisms that take into account both global trends and local challenges that can significantly change the business environment.
Keywords: marketing strategies; business resilience; consumer behavior; adaptation; green economy; flexibility; change management